I Am Thou, Thou Art I: Persona 5: The Royal’s: Representation of Post-Traumatic Growth Through Social Penetration Theory - Daniel Jr., Emory S.; Hays, Sarah; Bean, Anthony (Journal of Psychology and Psychotherapy Research, 2024)
In the Shin Megami Tensei series – Persona, one of the most prevalent themes that exists within the gameplay is the social link system. The protagonist creates friendships over the course of the narrative and deepens the bond with friends with increased interactions. As the number of interactions increase, so does the depth of the conversation. This study investigates the following objectives: 1) analyze how social interactions are presented in an in-game medium by means of social penetration, 2) determine how trauma is presented in Persona 5: The Royal and show how it is communicated as the relationship deepens, and 3) investigate frequencies of interactions between the protagonist and NPC’s as they demonstrate a coping mechanism through the means of post-traumatic growth. This case study will content analyze through the lens of coding categories such as Social Penetration Theory and the Post Traumatic Growth Index. Using these coding categories, authors will quantitatively analyze all confidant interactions through 10 levels of individual conversations increasing in depth. A content analysis was used to investigate these in-game themes. Using frequencies and Chi Square analysis, Affective stage and Stable stage from social penetration was the most frequent amongst the interactions, and while various trauma was present, Relating to Others was most prominent as the relationships deepened. The depths of interaction and coping through trauma was found to be quite similar to real world interactions and growing past trauma as a person relies on friends and family, and focuses on the future. These themes can be used to explain post traumatic growth, and could be utilized to empathize with clients who might be struggling with their own trauma.